2009
DOI: 10.3892/or_00000493
|View full text |Cite
|
Sign up to set email alerts
|

A scoring system for histopathologic and immunohistochemical evaluations of uterine leiomyosarcomas

Abstract: Abstract. Uterine leiomyosarcomas (LMS) are difficult to distinguish from benign leiomyomas without surgery. In this study we performed transcervical needle biopsy on 475 patients, 8 LMS patients and 467 patients with nonsarcomas (non-LMS) in a high-risk group for LMS, and evaluated whether examinations performed with Ki-67 and CD34 immunohistochemical analyses in addition to the standard hematoxylin-eosin (H&E)-stained sections would improve preoperative diagnostic precision of the uterine smooth muscle tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…In the IHC evaluation of Ki-67 using surgical specimens, all LMS specimens showed an LI of ≥15%. Therefore, we classified the Ki-67 LI as 5% and 15% [8]. In the present study, the expression of Ki-67 was high in LMS, but there was no difference between AL and LMS.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In the IHC evaluation of Ki-67 using surgical specimens, all LMS specimens showed an LI of ≥15%. Therefore, we classified the Ki-67 LI as 5% and 15% [8]. In the present study, the expression of Ki-67 was high in LMS, but there was no difference between AL and LMS.…”
Section: Discussionmentioning
confidence: 63%
“…The sections were counterstained with Mayer's hematoxylin. The specificity of the IHC reactions was checked by omitting the primary antibody [8]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, CD34-stained vessels were counted for each specimen at high-power fields (magnification, x40) and the highest number of positive vessels was recorded. We found that ~80% of leiomyosarcomas exhibit >10 CD34-stained vessels in necrotic areas and that the highest combined sensitivity and specificity is achieved by setting the cut-off score at 10 CD34-stained vessels (8). None of the smooth muscle tumors of uncertain malignant potential examined in the hospital of Osaka City University have exhibited coagulative tumor cell necrosis, thus, this combination is likely to be rare.…”
Section: Discussionmentioning
confidence: 80%
“…For angiogenesis immunoreaction, we used the CD34 monoclonal mouse antibody (Dako, 1:50 dilution) diluted in 1% BSA in PBS. We defined the scores of CD34 expression as negative, 0 points (Grade 0), mild 1 point (Grade 1), moderate 2 points (Grade 2), and severe 3 points (Grade 3) [ 28 ]. The intensity of staining was recorded as weak, moderate, and strong [ 29 ].…”
Section: Methodsmentioning
confidence: 99%